The Graveyard Book - Gaiman, Neil; McKean, Dave. (New York : HarperCollins Pub., 2008)
Nobody Owens is a normal boy, except that he has been raised by ghosts and other denizens of the graveyard.
Keywords: Dead -- Fiction; Supernatural -- Fiction; Cemeteries -- Fiction